Critical success factors influencing business intelligence adoption: Evidence from Yemen - Amira Taha Al-Adimi; Mokhtar Mohammed Ghilan; Walid Shaher Yousef; Abdullatif Ghallab (PLoS ONE, 2026)
Over the past five decades, decision support systems have evolved into business intelligence (BI) systems, which are now a strategic priority for many organizations. However, despite their widespread adoption, many BI projects fail, highlighting the need to identify Critical Success Factors (CSFs). While CSFs are well-studied in developed economies, there is a significant lack of empirical research in developing countries, which face unique challenges. This gap is particularly evident in Yemen, where BI adoption is still in its early stages of adoption. This study addresses this gap by investigating the CSFs for BI adoption in the Yemeni context. To do this, we develop and validate a novel integrated TOEP framework by combining the Technology-Organization-Environment (TOE) framework with the process-oriented Yeoh and Koronios model. Furthermore, we employ the rigorous Rough Stepwise Weight Assessment Ratio Analysis (R-SWARA) method, a multi-criteria decision-making approach adept at handling expert judgment uncertainty, to rank the CSFs. The results reveal that competitive pressure, data quality, clear vision, and change management are the most significant drivers in Yemen. However, in contrast to stable economies, information-sharing culture and system integration are currently the greatest challenges to these systems in the Yemeni context. The findings provide actionable insights for managers and policymakers in similar challenging environments, offering a contextualized model for successful BI adoption.